Drug-induced alterations in tumour perfusion yield increases in tumour cell radiosensitivity - Bennewith, K L (Nature Publishing Group, 2001)
The perfusion of human tumour xenografts was manipulated by administration of diltiazem and pentoxifylline, and the extent that observed changes in tumour perfusion altered tumour radiosensitivity was determined. 2 tumour systems having intrinsically different types of hypoxia were studied. The responses of SiHa tumours, which have essentially no transient hypoxia, were compared to the responses of WiDr tumours, which contain chronically and transiently hypoxic cells. We found that relatively modest increases in net tumour perfusion increased tumour cell radiosensitivity in WiDr tumours to a greater extent than in SiHa tumours. Moreover, redistribution of blood flow within WiDr tumours was observed on a micro-regional level that was largely independent of changes in net tumour perfusion. Through fluorescence-activated cell sorting coupled with an in vivo–in vitro cloning assay, increases in the radiosensitivity of WiDr tumour cells at intermediate levels of oxygenation were observed, consistent with the expectation that a redistribution of tumour blood flow had increased oxygen delivery to transiently hypoxic tumour cells. Our data therefore suggest that drug-induced changes in tumour micro-perfusion can alter the radiosensitivity of transiently hypoxic tumour cells, and that increasing the radiosensitivity of tumour cells at intermediate levels of oxygenation is therapeutically relevant. © 2001 Cancer Research Campaign   http://www.bjcancer.com